Pengaruh Kepuasan Kerja dan Komitmen Organisasi terhadap Organizational Citizenship Behavior (OCB) pada Karyawan Divisi Stamping bagian Produksi PT. XYZ - Anisa, Reni; Khaerul Rizal Abdurahman (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to analyze the influence of job satisfaction and organizational commitment on organizational citizenship behavior (OCB) on employees of the stamping division of PT. XYZ. The research method uses a quantitative approach with descriptive-associative techniques, involving questionnaires and interviews with 57 respondents. Data were analyzed through validity tests, reliability tests, classical assumption tests, multiple linear regressions, and hypothesis tests using SPSS. The results of the study indicate that both job satisfaction and organizational commitment have a significant positive effect on OCB partially and simultaneously. The contribution of these two variables to OCB reaches 88.4%, while 11.6% is influenced by other factors. This finding indicates that increasing job satisfaction and organizational commitment will encourage employee voluntary behavior that exceeds their formal responsibilities, thereby increasing the effectiveness and efficiency of PT. XYZ operations.  Keywords: Job Satisfaction, Organizational Commitment, Organizational Citizenship Behavior